Non-Peaceful Means of Exercising the Right of Peoples to Self-Determination"A Study in Light of the Rules of Contemporary International Law" - Najib Abdullah Muhammad Al-Tawati Shamilah (Journal of Scientific and Human Dimensions, 2026)
This paper, through the analytical approach, aims to examine national liberation movements, the legal basis for the legitimacy of such movements, their international legal personality, and certain legal obstacles related to the exercise by national liberation movements of the right of peoples to self-determination.National liberation movements possess several fundamental characteristics and essential elements. Primarily, they are organizations directed against foreign colonial powers occupying a given territory. They adopt a dual strategy combining armed struggle and political resistance in pursuit of self-determination. Furthermore, they rely on an active and effective popular base that includes various sectors of society, such as workers, students, women, and others. These movements seek to achieve a principal objective: full independence in its political, economic, social, and cultural dimensions. The paper also addresses whether Hezbollah may be considered among national liberation movements.
Keywords: Right; Peoples; Self-Determination; Hezbollah